2008
DOI: 10.2174/1874375700802010071
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Extrahepatic Cholestasis in the Rat: A Histopathological Liver Study

Abstract: Fibrosis, bile duct proliferation and mast cell hyperplasia characterize extrahepatic cholestasis. We studied these liver alterations in a new microsurgical model of extrahepatic cholestasis in the rat. Male Wistar rats: Sham-operated (n=9) and Microsurgical Cholestasis (n=10). After 4 weeks, a liver morphometric study was carried out using an image analysis system to assess bile proliferation and the fibrosis. The liver expression of alpha-smooth muscle actin was assayed by an immunohistochemical technique an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…There is evidence that mast cells are involved in various hepatobiliary disorders, such as chronic liver diseases and biliary/cholestatic diseases [34,35]. This suggests that they are at least involved in inflammation and periportal fibrosis [12,[35][36][37]. In addition, mast cells produce cytokines and growth factors that can promote excessive biliary epithelial cells proliferation [29].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that mast cells are involved in various hepatobiliary disorders, such as chronic liver diseases and biliary/cholestatic diseases [34,35]. This suggests that they are at least involved in inflammation and periportal fibrosis [12,[35][36][37]. In addition, mast cells produce cytokines and growth factors that can promote excessive biliary epithelial cells proliferation [29].…”
Section: Article In Pressmentioning
confidence: 99%
“…It was suggested that mast cells, involved in both innate and adaptive immunity [10,11], could be correlated with the evolution of experimental portal hypertension [2] and experimental hepatic chronic disease [1,12]. This is the reason why we have studied the hepatic-spleen-intestinal and mesenteric lymph node distribution of mucosal mast cells (MMCs) and connective tissue mast cells (CTMCs) in an experimental model of chronic liver insufficiency secondary to microsurgical obstructive cholestasis in the rat [13].…”
Section: Introductionmentioning
confidence: 99%